Human RNA methyltransferase BCDIN3D regulates microRNA processing - Xhemalce, Blerta (2012)
MicroRNAs regulate key biological processes and their aberrant expression may lead to cancer. The primary transcript of canonical miRNAs is sequentially cleaved by the RNase III enzymes, Drosha and Dicer, which generate 5′mono-phosphate ends that are important for subsequent miRNA functions. In particular, the recognition of the 5′mono-phosphate of pre-miRNAs by Dicer is important for precise and effective biogenesis of miRNAs. Here we identify a RNA-methyltransferase, BCDIN3D, that O-methylates this 5′mono-phosphate and negatively regulates miRNA maturation. Specifically, we show that BCDIN3D phospho-dimethylates pre-miR-145 both in vitro and in vivo and that phospho-dimethylated pre-miR-145 displays reduced processing by Dicer in vitro. Consistently, BCDIN3D depletion leads to lower pre-miR-145 and concomitantly increased mature miR-145 levels in breast cancer cells, which suppresses their tumorigenic phenotypes. Together, our results uncover a miRNA methylation pathway potentially involved in cancer that antagonizes the Dicer–dependent processing of miR-145 as well as other miRNAs.